„Nie może pozostawać duch mój w człowieku na zawsze” (Rdz 6,3). Długość ludzkiego życia na podstawie genealogii w Rdz 1–11 - Napora, Krzysztof (Verbum Vitae, 2013)
The Genealogies in the Book of Genesis present a challenge not only for common readers of the Holy Scripture but also for biblical scholars. For the former ones, their monotony slows down or even interrupts the flow of narration; for the latter ones, the genealogies’ monotonous rhythm can be a code to a theological enigma hidden in the holy text. One of the riddles in the genealogies of the Book of Genesis seems to be the shortening of human longevity between Gen 5 and Gen 11. Instead of looking for the causes of this process in human sinfulness or in human drifting apart from the garden of Eden, the author perceives this change as a result of God’s decision expressed in Gen 6:3.